Obravnava anemije pri bolnikih s srčnim popuščanjem - Šebeštjen, Miran (Zdravniški vestnik, 2010)
The prevalence of anemia in patients with advanced heart failure is significant and is present in more than 50 % of this patient population. The exact pathophysiologic mechanism of anemia in heart failure is still not known- it could be a direct consequence of the heart failure or it could be caused by some other disease in this population of polymorbid patients. There are several mechanisms through which heart failure could contribute to the development of anemia. The most plausible among them are hemodilution, renal insuffi ciency, increased proinflammatory cytokines, malnutrition, decreased erhythropoiesis in bone marrow and heart-failure medications (predominantly ACEI). Anemia is an independant risk factor for recurrent hospitalizations andincreased mortality. Several small-scale studies demonstrated that the treatment of anemia in heart-failure patients decreased heart failure signs and symptoms in this patient population. Anemia in heart-failure patients can be treated with: blood transfusion, iron replacement therapy, or with synthetic analogues of erhythropoietin. Before the treatment with synthetic analogues of erhythropoietin. is started, other causes of anemia (gastrointestinal bleeding, malnutrition, renal insuffi ciency, hematological diseases and malignancies) have to be excluded. Iron blood levels, ferritin, transferrin and TIBC also have to be determined. If body iron stores are depleted, iron has to be replaced intravenously, the target levels of ferritinbeing around 250 ng/mL. If anemia persists after 2 weeks of iron replacement therapy, treatment with erhythropoietin is indicated. Currently 4 erhythropoietin analogues are available: epoetin alpha (EprexR), epoetin beta (NeoRecormon R), darbepoetin alpha (AranespR) and metoksipolietilenglikol epoetin beta (MirceraR). Anemia needs to be treated in all NYHA III and IV heart failure patients and hemoglobin levels below 110 g/dL. (Abstract truncated at 2000 characters)
Keywords: Anemia; Anemija; Eritrocitna transfuzija; Eritropoietin; Erythrocyte Transfusion; Erythropoietin; Heart Failure, Congestive; Iron; Srce, odpoved kongestivna; srčno popuščanje; therapy; Treatment Outcome; zdravljenje; Zdravljenje, izid; Železo